2019
DOI: 10.3390/agriculture9090189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Late-Maturing Peach and Nectarine Fruit Quality by Chemical, Physical, and Sensory Determinations

Abstract: In this work, both analytical and sensory determinations were carried out to evaluate the quality of yellow (‘Summerset‘, ‘Tardiva 2000‘, ‘Fairtime”, ‘Guglielmina’) and white flesh (‘Daniela’) late-ripening peach and nectarine (‘California’ and ‘Fairlane’) cultivars. Analytical measurements included weight, diameter, soluble solid content, titratable acidity, pH, and peel color. To describe and quantify the peach and nectarine sensory profile, a panel of 10 judges generated 15 descriptors. According to univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…The results are comparable to the ones documented by Botoran et al [ 44 ] concerning the amino acid profile of selected fruits, including peaches from unknown varieties. In addition, Farina et al [ 45 ] found that varieties with large and attractive fruit often lacked real nutritional quality.…”
Section: Resultsmentioning
confidence: 99%
“…The results are comparable to the ones documented by Botoran et al [ 44 ] concerning the amino acid profile of selected fruits, including peaches from unknown varieties. In addition, Farina et al [ 45 ] found that varieties with large and attractive fruit often lacked real nutritional quality.…”
Section: Resultsmentioning
confidence: 99%
“…While the high levels of hue and lightness (L* = 78.5; data not shown), along with the low levels of chroma in ‘Ghiaccio 1’ describe well the anthocyianinless nature of this genotype (completely white exocarp and mesocarp). Overcolor coloration did not associate with high-eating quality traits in a previous sensory panel [ 73 ]. Regardless, this sensory panel did not evaluate fruit appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Titratable acidity and soluble solids are important characteristics for industry, and the balance between these two components is associated with the quality and flavour of the fruits (Farina et al., 2019). The results obtained in our study showed little variation in SS (10.11 to 13.48 °Brix) and TA (3.68% to 3.85%) in the BC2 progeny evaluated, although these values are within the minimum standards recommended by Brazilian regulations, which are 11.0 °Brix and 2.50% TA.…”
Section: Discussionmentioning
confidence: 99%